Comparing the effectiveness of pregabalin and duloxetine in the management of neuropathic pain - Hamed Ali, Rojgar; Shafeeq Tawfeeq, Govand; Mohsin Mustafa, Amanj; Abdulmanaf Shakir, Shayma; Ghanim Salem, Najat; Idrees Swedi, Aswan (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Neuropathic pain is a type of pain that originates from damage or dysfunction of the somatosensory nervous system. Managing neuropathic pain is a challenging task as it is chronic and has limited treatment options. Pregabalin and duloxetine aim to alleviate neuropathic pain symptoms and enhance quality of life for patients. The comparative effectiveness of these drugs, particularly at lower doses that are typically provided in the Kurdistan Region of Iraq, is still a topic of inquiry that is presently being carried out. The objective of the study is to evaluate and compare the effectiveness of pregabalin and duloxetine on pain management and sleep quality in patients with neuropathic pain. Such insights are crucial for optimizing neuropathic pain management strategies and improving patient outcomes. Methods: in this prospective study, 80 patients displaying signs and symptoms of neuropathic pain such as sharp, stabbing, numbness, and/or burning pain as well as tingling, loss of balance and coordination, and/or muscle weakness, especially in the feet were prescribed either pregabalin (n=40) or duloxetine (n=40) with mean doses of 82.5± 5.16 mg/day and 34.5± 2.46 mg/day, respectively, administered once or twice daily for 4 weeks. The results were based on the effectiveness of the drugs in reducing visual analogue scale and pain related sleep interference scale scores. Results: Both pregabalin and duloxetine reduced the signs and symptoms of neuropathic pain, demonstrating similar efficacy within the first 3 weeks of the treatment. However, by the 4th week, duloxetine exhibited superior effectiveness in managing neuropathic pain (P = 0.001). On the other hand, findings showed no significant difference in the reduction of sleep scores (P = 0.978). Conclusion: Both pregabalin and duloxetine are similarly effective in managing neuropathic pain during the first 3 weeks of treatment. However, when the treatment duration extends beyond 3 weeks, duloxetine demonstrates superior effectiveness in reducing neuropathic symptoms.